Long-term effects of intercrops on growth, yield and fruit quality of plum (Prunus salicina) - KUMAR, JAYANT; RANA, S S; VERMA, H S; PARMAR, D K (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during 1988-99 at Bajaura, Himachal Pradesh, to study the effect of 8 intercrop combinations, viz wheat (Triticum aestivum L. emend. Fiori & Paol.)-maize (zea mays L.) pea (Pisum sativum L. var arvense L.)-tomato (Lycopersicon esculentum Miller nom. cons), lentil (Lens culinaris Medikus)-blackgram, (Phaseolus mungo L.), lentil-maize, wheat-blackgrame clover (Trifolium repens L.) setaria (Seteria anceps Stapf ex Massey) and control, on growth, yield and fruit quality of 'Santa Rosa' plum (Prunus salicina Lindley) grafted on wild aprocot (Prunus armeniaca L.) rootstocks. the highest trunk girth (59.7 cm), shoot length (132.9 cm) and fruit yield (86.4 kg/tree) were observed with pea- tomato intercrop, following by lentil-blackgram. The lowest trunk girth (41.2 cm), shoot lenght (87.2cm) and fruit yield (41.2 kg/tree) were recorded with setaria grass. The treatment pea- tomatao also resulted in the highest fruit length (4.82 cm), breadth (4.93 cm) and fruit weight (67.7 g.). The lowest fruit length (4.37), breadth (4.22 cm) and fruit weight (49.3 g) were observed with setaria grass, However, the control resulted in the highest total soluble solids (13.8oB), reducingÂ  sugars (5.54%) and total sugars (6.75% ). Titratable acidity could not be influenced by the treatments.